Simulated moving bed technology : principles, design and process applications - Rodrigues, A. E. (Butterworth-Heinemann, 2015)
This book aims to equip you with the tools and skills needed for simulated moving bed technology (SMB) modelling, simulation, design and operation. The theory presented is supported by real-world examples from the petrochemical, sugar and pharma industries. It focuses on SMB process development and model validation and explains basic process concepts and definitions, fundamental principles and equations, as well as typical applications and recent advances made to address challenges. Process intensification through coupling SMB and reaction in SMBR, membrane permeation and SMBR in PermSMBR, and the design of SCPC are discussed. --